Virtual wine experiences: Is covid extending the boundaries of wine tourism? - Giulia Gastaldello; Elisa Giampietri; Elena Zaghini; Luca Rossetto (Wine Economics and Policy, 2022)
Wine tourism has long been a strategic tool for Italian wineries. The Covid-19 outbreak jeopardised its dynamics on multiple levels, creating physical (e.g., social distancing, travel bans) and psychological barriers. Online wine experiences constitute one of the key resilience strategies adopted by wine tourism actors, being still a relatively unexplored phenomenon in the scientific literature. The current study tackles this gap by analysing the drivers of interest in online wine experiences on the demand side, i.e. among a sample of Italian wine tourists (n=408), through Structural Equation Modelling (SEM). Notably, the model considers long-term (involvement with wine) and short-term (Covid-19 fear and anxiety) factors, digitalisation and willingness to support local wineries by partaking in wine tourism. Results highlight that the interest in online wine experiences is driven by context-dependent factors like fear and anxiety linked to Covid-19, and the involvement with wine. Diversely, willingness to go on a wine holiday is not a significant antecedent, even with Covid-19 fear and anxiety as limiting factors. Practical and managerial implications are discussed.
Keywords: 330; virtual wine tourism; online experience; Covid-19